The Versatile Gasdermin Family: Their Function and Roles in Diseases - Zou, Ju; Zheng, Yixiang; Huang, Yan; Tang, Daolin; Kang, Rui; Chen, Ruochan (Frontiers in Immunology, 2021)
The gasdermin (GSDM) family, a novel group of structure-related proteins, consists of GSDMA, GSDMB, GSDMC, GSDMD, GSDME/DNFA5, and PVJK/GSDMF. GSDMs possess a C-terminal repressor domain, cytotoxic N-terminal domain, and flexible linker domain (except for GSDMF). The GSDM-NT domain can be cleaved and released to form large oligomeric pores in the membrane that facilitate pyroptosis. The emerging roles of GSDMs include the regulation of various physiological and pathological processes, such as cell differentiation, coagulation, inflammation, and tumorigenesis. Here, we introduce the basic structure, activation, and expression patterns of GSDMs, summarize their biological and pathological functions, and explore their regulatory mechanisms in health and disease. This review provides a reference for the development of GSDM-targeted drugs to treat various inflammatory and tissue damage-related conditions.